Effect of different blood flow meters and diets on volatile fatly acids and other metabolites into portal blood of sheep - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT The aim of the study was to observe effect of diets composition and portal blood flow ioeters on net portal appearance of acetate and other key-nutrients. Three Merino wethers were fed either lucerne chaff: oaten hay (40:60, UOC)